Permanent Layoffs and Displaced Workers: Cyclical Sensitivity, Concentration, and Experience Following the Layoff - Picot, G.; Pyper, W. (Journal of Income Distribution®, 1994)
Concern about permanent layoffs and the experience of displaced workers is high because of the restructuring in firms currently taking place, and the effect of changes in international trade on some industries, often leading to layoffs. Our understanding of permanent layoffs has been hampered by the lack of appropriate data until recently. This paper uses two relatively new sources of data to examine (1) the variation in permanent layoffs over the business cycle, primarily to determine their significance during the expansionary periods when decreases in aggregate demand play little role in the layoff process, (2) where permanent layoff are concentrated in the economy during expansionary periods when restructuring and the competitive process play the major role in layoffs, and (3) the labor market experiences of displaced workers following the layoff.